Respostas

2014-04-14T19:12:45-03:00
A) x²+2x-8=0    a= 1         b= 2         c= -8
Δ= b² - 4ac
Δ= 2² - 4(1)(-8)
Δ=4 + 32
Δ=  36    se Δ>0     então x= -b +-√Δ/2a

x' = -2 -√36/2(1)
x' = -2 - 6/2   ------------ x' = - 8/2           x'= -4
x" = -2 + 6/2 --------------x" = 4/2            x" = 2

b) -x²+10x-24=0             a= -1              b=10           c= -24
Δ= b² - 4ac
Δ= 10² -4(-1)(-24)
Δ= 100 - 96
Δ= 4 se    Δ>0       x= -b +-√Δ/2a
x' = -10 -√4/2(-1)
x' = -10 -2/-2    ---------------- x'= -12/-2-------------x' = +6

x" = -10 + 2/-2  -------x' = -8/-2 -----------------------x" = +4


c)-x²-2x+3=0                a=-1               b=-2              c= 3
Δ= b² -4ac
Δ= (-2)² - 4(-1)(3)
Δ= 4 + 12
Δ= 16     se     Δ>0    então x= -b + - √Δ/2a
x' = -(-2) -√16/2(-1)
x'= 2 -4/-2 ------------------------x' = -2/-2  -------x' = +1
x" = -(-2) + 4/-2------------------x" = 2+4/-2--------x" = 6/-2---------x" = -3



d) x²+4x+4=0         a= 1        b=4          c=4
Δ= b² - 4ac
Δ= 4² - 4(1)(4)
Δ= 16 - 16
Δ = 0       então  x= -b/2a

x= - b/2a
x = -4/2(1)
x =  -4/2
x = - 2


e) 3x²-8x+10=0     a= 3        b= -8       c= 10
Δ= b² - 4ac
Δ= (-8)² - 4(3)(10)
Δ= 64 -120
Δ= - 56        se   Δ<0    então    V =Ф